2019
DOI: 10.1002/cplu.201900303
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Sulfur Co‐Doped Mesoporous Carbon Embedded with Co9S8 Nanoparticles: Efficient Electrocatalysts for Hydrogen Evolution

Abstract: Co9S8 embedded, N,S co‐doepd mesoporous carbon materials were synthesized by adopting CoCl2 as the molten salt. In details, CoCl2 and glucose were used as cobalt and carbon precursors, respectively, and thiourea was utilized as sulfur and nitrogen precursors. This synthetic process involved three steps, including hand‐milling, carbonation, and acid leaching. The results of characterization exhibited that the final products had mesoporous structures, which also showed high nitrogen and sulfur contents. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…In summary, the above results confirm that similar to the pyrolysis of polyhydroxy compounds, [46][47][48] PEG200 and thiourea can be converted into carbon materials co-doped with nitrogen, sulfur and oxygen. The calcination process inevitably leads to the formation of oxygen vacancies or sulfur vacancies, providing anchor sites for nanoparticles.…”
Section: Formation Of Desssupporting
confidence: 70%
“…In summary, the above results confirm that similar to the pyrolysis of polyhydroxy compounds, [46][47][48] PEG200 and thiourea can be converted into carbon materials co-doped with nitrogen, sulfur and oxygen. The calcination process inevitably leads to the formation of oxygen vacancies or sulfur vacancies, providing anchor sites for nanoparticles.…”
Section: Formation Of Desssupporting
confidence: 70%
“…Using inorganic salt as a template, Yu prepared a series of Co 9 S 8 nanoparticles embedded with N and S co-doped carbon through three steps of grinding, carbonation and acid leaching (Figure 2c). It is suggested that the ratio of precursor, annealing temperature and the type of salt can adjust the porosity, heteroatomic content and crystal structure of the product [26][27][28]. Different synthesis methods have different advantages.…”
Section: Zero-dimensional (0d) Structurementioning
confidence: 99%
“…[24,25] In our prior reports, various cobalt sulfide-based electrocatalysts for HER were synthesized via the molten salts process, which possessed outstanding HER performance due to high surface area and pore volume (Table S1). [26][27][28][29] However, with the rapid development of lithium-ion battery industry, the price of cobalt-containing minerals and raw materials remains high. Doping some transition metals with lower price in cobalt sulfide material can greatly reduce the synthesis cost of catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of these inorganic salts can reduce the synthesis cost, which can also be recycled [24,25] . In our prior reports, various cobalt sulfide‐based electrocatalysts for HER were synthesized via the molten salts process, which possessed outstanding HER performance due to high surface area and pore volume (Table S1) [26–29] . However, with the rapid development of lithium‐ion battery industry, the price of cobalt‐containing minerals and raw materials remains high.…”
Section: Introductionmentioning
confidence: 99%